If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1 = 13 + -1x Reorder the terms: -1 + 6x = 13 + -1x Solving -1 + 6x = 13 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -1 + 6x + x = 13 + -1x + x Combine like terms: 6x + x = 7x -1 + 7x = 13 + -1x + x Combine like terms: -1x + x = 0 -1 + 7x = 13 + 0 -1 + 7x = 13 Add '1' to each side of the equation. -1 + 1 + 7x = 13 + 1 Combine like terms: -1 + 1 = 0 0 + 7x = 13 + 1 7x = 13 + 1 Combine like terms: 13 + 1 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| 5x-12=4x+29 | | ln(x)=3.06 | | 3x-4-x=4 | | 8a-b-3a-2b= | | 25=1.2x+9 | | -37=-6-7 | | x+(y+3)=13 | | 5x-14=19-6x | | v=17*2*1 | | (3x)w=30 | | 2+6x+x=30 | | 2.1x-1=x+11.1 | | X^2-4x-500=0 | | 21=-x | | x+(2x+15)+(x+15)=180 | | -4+4x-5x=1 | | 6X-11=8X+10 | | .2x+9+.8x=-11 | | 12m+6n-5m+8n= | | k=v+29 | | 4(x+9)+3=9x-5(x-3) | | -5(x+4)+98=28+10 | | 10a=7 | | 2y+12=-2 | | -5x+10+4x=0 | | 2a+3b-c=18 | | 3x=-2x^2 | | 2X+94=10X-10 | | -3x-(-4)=3x+10 | | 123456789012345678901234567890+98765432109876543210987654321= 222222221122222222112222222211 | | 15+15x=180 | | (3x-5)(3x-5)=26 |